SURGICAL TREATMENT OF GINGIVAL RECESSION WITH SOFT TISSUE GRAFT PROCEDURE - Denislav Emilov; Elitsa Deliverska (Peytchinski Publishing, 2018)
Periodontal plastic surgery is part of mucogingival therapy. The aim of this surgical procedure is to prevent or correct anatomic, developmental, traumatic or disease-induced defects of the gingiva, alveolar mucosa or bone. This definition includes various soft- and hard-tissue procedures aimed at gingival augmentation, root coverage, correction of mucosal defects at implants, crown lengthening, gingival preservation at ectopic tooth eruption, removal of aberrant frenum, prevention of ridge collapse associated with tooth extraction and augmentation of the edentulous ridge. This review focuses on gingival recession defects, their diagnosis and prognosis and the surgical procedures for root coverage. Etiology of gingival recession is multifactorial and include: anatomical, physiological and pathological factors. The treatment of gingival recession defects is indicated for esthetic reasons, to reduce root hypersensitivity and to create or augment keratinized tissue. Gingival recession can be treated with various surgical procedures, and root coverage can be obtained irrespective of the surgical approach adopted.